SOCIO-PSYCHOLOGICAL APPROACHES TO THE DEFINITION OF TERRORISM - E. B. Batueva (Вестник университета)
The results of a theoretical and empirical study of the definition of “terrorism” have been presented. As a result of the analysis of works devoted to the psychology of terrorism, five approaches to the definition of terrorism have been distinguished: terrorism as a form of activity; terrorism as a communicative strategy; terrorism as a form of war; terrorism as a form of conflict; terrorism as a form of extremism. Respondents’ associations related to the concept of “terrorism” have been analysed. Three groups of associations with this consept have been emphasized: characteristics, motivations, and consequences of terrorism. Characteristics are related to the assessment of terrorism, the identity of the terrorist, and attitudes to terrorism. Motivations are divided into personal, interpersonal and social. The consequences are manifested at the level of the individual, social group and society. The classification is based on the orientation of associations: negative, neutral (ambiguous) and positive (exculpatory). Emotional, rational and value  components of the attitude to terrorism also have been highlighted.